The fragility of cooperation: A false feedback study of a sequential iterated prisoner's dilemma - Monterosso, John; Ainslie, George; Pamela Toppi Mullen, P.A.-C; Gault, Barbara (Journal of economic psychology, 2002)
We examined the mutability of naturally occurring mutual cooperation and mutual defection. Forty-five pairs of subjects participated in an extended iterated prisoner's dilemma (median duration 1807 trials) using a monetary payoff matrix. When stable cooperation or defection emerged, false feedback was provided indicating to each subject that his partner was choosing contrary to previously stable play. This was followed by recovery trials in which false feedback indicated to each subject that his partner had resumed making the previously stable choice. While stable cooperation occurred more frequently than stable defection, it was considerably more vulnerable to the false feedback manipulation. This was true both in terms of the extent to which choice changed in response to false feedback ( p=0.006) and in terms of the extent to which the disruption persisted ( p<0.001). While the effect of four false feedback cooperations was undone by a single recovery false feedback defection, the effect of even a single false feedback defection was still apparent after seven false feedback recovery cooperations. These results are discussed in relation to the analogy between interpersonal bargaining and intertemporal bargaining within individuals.